Pengembangan Media E-Book untuk Materi Morfem Bebas dan Terikat pada Mata Pelajaran Bahasa Indonesia - Nadia Nadila; Ayu Nafira; Herawati Herawati; Lidia Agnesia Lumban Batu (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
To improve the understanding of fifth grade elementary school students about the material of free morphemes and bound morphemes, this type of research is research and development (R&D). The results of the preliminary study showed that there was no learning media that facilitated learning and that students did not understand free morphemes and bound morphemes. Based on these findings, the author plans to create an illustrated e-book called "The Adventures of Bound and Free Morphemes" to improve students' understanding in fifth grade elementary school. The results of the validation of the first material expert and media expert showed that the e-book received a score of 70.7% and was included in the category. Thus, it can be concluded that the e-book is valid and practical to use to improve students' understanding.